Analysis of Junior High School Teacher's Professional Commitment with Digital Literature Perspective and Self-Efficiency - Erni Murniarti; Hotmaulina Sihotang; Vitry Marenden (International Journal of Artificial Intelligence Research, 2022)
One aspect that contributes to the quality of education in Indonesia, which is still low, is the commitment of the teaching profession to carry out the work. Based on the data and direct observation, it was found that the professional commitment of the teacher was quite good but not optimal. This study aims to analyze the positive and significant influence of digital literacy on the commitment of the teaching profession in the Rantepao District. The survey is quantitative to find factual facts in decision-making. With a population of State Junior High School teachers in the Rantepao sub-district and the research, the sample is 122 state ASN teachers in Rantepao District, using a questionnaire instrument. The instrument was validated by experts and tested on 30 teachers of ASN 3 SMP Negeri in North Toraja Regency to obtain a valid and reliable instrument. Based on the analysis results obtained conclusions through a simple regression equation = 1.840 + 0,600X. The digital literacy regression coefficient is positive at 0.600 with a sig value of 0.002. smaller than Î±= 0,05. There is a positive and significant effect of digital literacy on the commitment of the teaching profession by 33.3%, and other factors influence the rest.